The housing problem in light of the Syrian crisis and its repercussions on family stability - A field study of the city of Jaramana in the Damascus countryside governorate - - Jalb, Nihal Abdulsalam Rehawi (Journal of Humanities & Social Sciences, 2021)
The study aimed to describe the reality of the housing problem that displaced families suffer from in the city of Jaramana in light of the Syrian crisis and to identify the economic and social repercussions of the housing problem on stability among the responses of the sample families about the implications of the housing problem on family stability according to a number of variables (education level of the Lord The family, the work of the head of the family, and the income of the family), and the study adopted the descriptive-analytical approach, and a questionnaire was adopted as a tool to collect information, and it was applied to a sample of the displaced families within the city of Jaramana in the Damascus countryside governorate, and the sample consisted of sixty displaced families. The study found several conclusions, including: the largest percentage of economic repercussions were the difficulty in obtaining housing, followed by the percentage of inability to secure family requirements and the inability to pay the monthly rent, and with regard to the social repercussions, the largest percentages were for the lower educational level of children and the lack of privacy in the relationship between spouses, Regarding to the conclusion the study it is recommended several recommendations, including: Building temporary housing units equipped with all the supplies and needs to be distributed to the displaced families to meet the urgent increases of the displaced and reduce the severity of housing rents.
Keywords: housing; economic growth; family; family stability